(untitled) (Research, Society and Development, 2020)
The cultivation of mulberry has shown great growth over the years due to its low cost of production and health benefits. It is of great interest to the food industry since it has almost full use of all its components from its fruits to its stem and leaves. The consumption of capsules and leaves has alterations in their antioxidant functions, consequently, increased consumption of blackberry leaf infusions with great prominence. In this study, the parameters applied for the blackberry leaf infusion were the infusion time, the extraction temperature and the leaf concentration as a function of water. The objective of the work was with these dependent variables to perform a Central Rotational Compound Design 2³ to verify the phytochemical properties of two different brands of blackberry leaves (Morus nigra L.). A phytochemical prospecting tested qualitatively with the presence of reducing sugar, alkaloid, amino acids, steroids, phenol, flavonoids, cardiac glycosides, saponins, tannins and terpenes. Regarding the phytochemical screening of extracts from the two brands (A and B), confirm the presence of phenols, flavonoids, cardiac glycosides, tannins, terpenes and saponins, however, only the B brand of these amino acids.